Material Writing for and in the EFL Setting - Oscar Molina Márquez (Asociación Colombiana de Profesores de Ingles, 2016)
The idea behind presenting a paper or a workshop at the XIX Annual English Language Teaching Symposium, at the Centro Colombo-Americano, sprang from my experience as both a teacher-trainer in Microteaching Sessions and a need to provide language teachers with some insights regarding materials development for and in the EFL setting.